2010
DOI: 10.1002/ange.200906232
|View full text |Cite
|
Sign up to set email alerts
|

Drug‐Free Macromolecular Therapeutics: Induction of Apoptosis by Coiled‐Coil‐Mediated Cross‐Linking of Antigens on the Cell Surface

Abstract: A new paradigm was designed for apoptosis induction mediated by the biorecognition of coiledcoil motifs at the Raji B cell surface. The heterodimerization of complementary peptides, one bound to Fab' antibody fragment, the other as grafts to HPMA copolymer, results in crosslinking of CD20 target antigens, and consequently, initiation of apoptosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
81
0
2

Year Published

2012
2012
2021
2021

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 42 publications
(83 citation statements)
references
References 27 publications
0
81
0
2
Order By: Relevance
“…The biorecognition of the coiled-coil forming oligopeptides, CCE and CCK, in the “drug-free” system worked well both in vitro 21,74 and in vivo. 72 However, to achieve a strong anticancer effect (produce tumor-free long-term survivors), we used a 1:25 molar ratio of CCE equivalent (in Fab′-CCE) to CCK equivalent (in P-(CCK) 9 ).…”
Section: Design Of Drug-free Macromolecular Therapeuticsmentioning
confidence: 98%
See 2 more Smart Citations
“…The biorecognition of the coiled-coil forming oligopeptides, CCE and CCK, in the “drug-free” system worked well both in vitro 21,74 and in vivo. 72 However, to achieve a strong anticancer effect (produce tumor-free long-term survivors), we used a 1:25 molar ratio of CCE equivalent (in Fab′-CCE) to CCK equivalent (in P-(CCK) 9 ).…”
Section: Design Of Drug-free Macromolecular Therapeuticsmentioning
confidence: 98%
“…In contrast, the CCE/CCK coiled-coil formation required a much longer time (~60 min). 21 Further analysis with UV-visible and CD spectroscopy indicated that such binding was indeed mediated by MORF1/MORF2 hybridization and that the melting temperature was about 59 °C, well above body temperature. These results suggested a fast and stable self-assembly of the two conjugates, which are favorable for the design of drug-free macromolecular therapeutics.…”
Section: Design Of Drug-free Macromolecular Therapeuticsmentioning
confidence: 98%
See 1 more Smart Citation
“…Aggregation von mit monound multivalenten Thiolen stabilisierten Goldnanopartikeln in Lçsung [67] hochauflçsende Flüssigkeitschromato-graphie (HPLC) [88] Weitere wichtige Beispiele für statistische multivalente Gerüstarchitekturen sind Glycopolymere. [89] Sie [90,91] Landers et al konnten zeigen, dass ein SA-konjugiertes Polyamidoamin-Dendrimer (G4-SA) geeignet ist, in vitro die Hämagglutination (Erythrocyten-VirusWechselwirkung) zu inhibieren, wenn die Sialinsäure über einen kurzen Spacer angebunden wird.…”
Section: Stabilität Gegen Aggregation Als Funktion Multivalenter Stabunclassified
“…CXCR4 antagonism by RPA does not require the polymer to be internalized, which is advantageous because no intracellular barriers need to be overcome. [13] However, because the CXCR4 receptor is not internalized in the presence of an antagonist like RPA, binding of RPA/DNA to this receptor Figure 2. CXCR4 antagonism of RPA and RPA/DNA polyplexes.…”
mentioning
confidence: 99%